TRADITIONAL PRACTICES ADOPTED BY JORDANIAN MOTHERS WHEN CARING FOR THEIR INFANTS IN RURAL AREAS - Al-Sagarat, Ahmad Yahya; Al-Kharabsheh, Amani (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Traditional practices are commonly present within the Jordanian society, especailly those concerned with infant’s care. Some of these practices might be harmful and thus health professioanls are required to substitute these practices with safe and healthy ones. The goal of this study is to determine the traditional practices adopted by Jordanian mothers when caring for their infants in rural areas. Materials and Methods: A descriptive study design using qualitative method was utilized in this study. A Purposive sample of 30 mothers was recruited from four rural regions in outskirts of Amman the capital city of Jordan. Results: Mothers had traditional infant’s care practices pertinent to bathing of babies, including the salting, swaddling, care of the umbilical cord and jaundice. Conclusion: Traditional practices are still common in Jordan; some of these behaviors can cause health risks. While health consequences of some of the traditional practices are still not clear, health professianls, especially nurses, are required to intervene by changing policies and education